2005
DOI: 10.1002/pssc.200461723
|View full text |Cite
|
Sign up to set email alerts
|

Features of arsenic clusters in silicon

Abstract: The solid solubility of As in silicon, the ionisation equilibria at different dopant concentrations and temperatures and the algorithms that describe these phenomena are reviewed and discussed. Experimental evidence of the occurrence of different types of clusters is presented. The correlation of clustering equilibria with As diffusivity is shown by suitable experiments. Finally we report and discuss the kinetics of As deactivation and the influence of excess point defects on the clustering process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is worth mentioning that if As concentration is higher than the solubility limit, the electrical properties of the heavily As-doped Si deteriorates due to the occurrence of electrically inactive arsenic clusters [ 125 , 132 , 133 ]. The electrically inactive cluster contains two As atoms and one vacancy position [ 125 , 134 ]. Furthermore, these clusters result in obstructing the phase equilibrium between Si and the AsSi compound by blocking the nucleation of AsSi precipitates.…”
Section: Phase Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that if As concentration is higher than the solubility limit, the electrical properties of the heavily As-doped Si deteriorates due to the occurrence of electrically inactive arsenic clusters [ 125 , 132 , 133 ]. The electrically inactive cluster contains two As atoms and one vacancy position [ 125 , 134 ]. Furthermore, these clusters result in obstructing the phase equilibrium between Si and the AsSi compound by blocking the nucleation of AsSi precipitates.…”
Section: Phase Diagramsmentioning
confidence: 99%
“…Hence, it is of great importance to determine the maximum solubility of As in Si precisely. Nobili and Slomi [ 134 ] described the maximum As concentration, C sat , in Si lattice at equilibrium with AsSi by based on the best fit equation given in Nobili’s earlier work [ 128 ] in the 800–1050 °C temperature range.…”
Section: Phase Diagramsmentioning
confidence: 99%
“…Various arsenic‐vacancy clusters as well as SiAs aggregates or precipitates were observed that contribute to the deactivation of arsenic. Even now, they are subjects of numerous experimental studies and first‐principles calculations 14–18. In spite of the large amount of scientific literature, the SiAs system is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Yet by increasing the dopant concentration the dopant becomes electrically inactive to some extent. Studies of the electrically inactive dopants in heavily doped Si are mainly done with wafers where the dopant is either thermally diffused into the wafer or doping takes place through ion implantation and a thermal treatment afterwards [1][2][3]. Clearly, the electrically inactive fraction of the dopant is influenced by the thermal history.…”
Section: Introductionmentioning
confidence: 99%